Chlorate ion mediated rutile to anatase reverse phase transformation in the TiO2 nanosystem - Bhosale, Reshma; Hyam, Rajeshkumar S.; Dhanya, P.; Ogale, Satishchandra B. (Dalton Transactions, 2011)
Rutile TiO2 nanoneedles (8 nm x 100 nm) synthesized at room temperature by anodization in perchloric acid (pH < 1) are shown to undergo an interesting reverse phase transformation to anatase nanoparticles (8 nm) at 300 degrees C only if the chlorate ions are maintained in the ambient medium. When chlorate ions are removed by multiple washing, the rutile phase and the needle morphology are maintained. The mechanism of formation of the ion-stabilized solid and its thermal evolution is discussed.